The Role of Immigration Intelligence of the Directorate General of Immigration in Preventing the Entry of Foreigners Who Have the Potential to Threaten the Sovereignty of the State - Andi Muhammad Syaqil Aswad Syadzili; Eko Daryanto; Stanislaus Riyanta (Eduvest - Journal of Universal Studies, 2025)
Immigration intelligence plays a vital role in safeguarding Indonesia’s borders from the potential negative impacts of foreign nationals’ mobility, which can lead to violations and crimes that threaten national sovereignty. The increasing complexity of transnational crimes, such as human trafficking, terrorism, and illegal migration, highlights the need for robust intelligence measures to ensure national security. However, there is still limited research analyzing the strategic functions of immigration intelligence in addressing these evolving challenges. This study aims to examine the roles and functions of immigration intelligence in conducting investigations and securing borders through intelligence operations. The research employs a qualitative descriptive method, using a literature review and analysis of relevant reports, legal frameworks, and operational documents. The findings reveal that immigration intelligence is crucial in collecting, processing, and analyzing information across ideological, political, economic, social, cultural, defense, and security dimensions to anticipate potential threats. Its preventive role is also emphasized, particularly in early detection and risk mitigation. The implications of this study underscore the need for strengthening coordination among immigration authorities and security agencies, as well as enhancing the use of advanced technologies to improve the effectiveness of intelligence operations.